Adrenal tumours: open surgery versus minimally invasive surgery. Issue 1 (January 2020) - Fiori, Cristian; Checcucci, Enrico; Amparore, Daniele; Cattaneo, Giovanni; Manfredi, Matteo; Porpiglia, Francesco
Abstract : Purpose of review: The aim of this article is to focus on state-of-the-art minimally invasive adrenalectomy (MIA) and the most recent role of open adrenalectomy for adrenal tumours, respect to MIA and open adrenalectomy for adrenocortical cancer (ACC). Recent findings: The laparoscopic (both transperitoneal and retroperitoneal) approach is the first-choice treatment in cases of small-to-medium benign adrenal tumours. This approach is feasible and well tolerated even for larger lesions without radiological signs of malignancy. Robotic adrenalectomy has recently increased in popularity, although the results appear to be fully comparable with those of laparoscopy. Open approach is the keystone of ACC surgery, especially when neighbour tissues, organs, or vessels are involved. Recent evidence suggests caution in treating localized ACC with laparoscopy, because of the higher rate of local or peritoneal recurrence, and shorter recurrence-free survival rates with respect to open adrenalectomy. Summary: MIA has progressively replaced the traditional open approach and plays a complementary role in the treatment of adrenal tumour. It is the first option for benign lesions, whereas open adrenalectomy is a cornerstone treatment for ACC. The overlap of indications for laparoscopic adrenalectomy and open adrenalectomy is today confined to the treatment of organ-confined adrenal cancer, in which the role of laparoscopic surgery is far from being clearly defined.